Analisis Pemanfaatan Perpustakaan Sekolah sebagai Sumber Belajar Peserta Didik di Sekolah Dasar Negeri 12 Pontianak Selatan - Susilawati, Yeni; Kresnadi, Hery; Salimi, Asmayani; Halidjah, Siti; Pranata, Rio (AS-SABIQUN, 2024)
This study aims to describe the utilization of the school library as a learning resource for students at State Elementary School 12 South Pontianak. The research method used was descriptive with a qualitative research form. The data sources of this research were Librarians and Teachers of State Elementary School 12 South Pontianak and the data were the results of interviews and observations with school Librarians and Teachers. The data collection techniques in this research were non-participatory observation techniques, semi-structured interview techniques, and documentation. The data collection instrument in this study was the researcher himself as the main instrument using observation guidelines, interview guidelines, and documentation. Based on the data from observations and interviews, the utilization of the school library as a learning resource for students has been well implemented. The supporting factors are school library facilities and infrastructure, access to the school library. While the inhibiting factors are the absence of library membership cards and interest students to utilize the school library as a learning resource.